Antropologia linguística & etnografia toponímica: vivências e narrativas em linguagens socioculturais de Murinin-Benevides-Pará - FARIAS, Maria Adelina Rodrigues de (Universidade Federal do Pará, 2017)
The present experiment deals with the questioning about the meaning of the names of places where people circulate, the toponyms, in the municipality of Benevides-PA, more precisely in the district of Murinin. The toponymic studies have as scope the deprehension of the lexicon of certain territories, considering the historical and socio-cultural formation of the people that live there, specifically through the names given to the social circulation places, such as streets, waterways, districts, cities, etc., evidencing both synchronic and diachronic aspects of speech. The study deals with a discussion about the construction of memory and toponymic identity of this locality, demonstrating the values attributed by the interlocutors to their birth and/or living places. The problematization is based on the following guiding question: What power relations are present in the constitution of this nominalization? For this reason, I considered, for this research, to work with the theoretical assumptions of Postcolonial Anthropology and the studies on Oral Narratives. Thus, I start, in principle, a formal survey, not escaping too much from the traditional methodology of toponymic research, but considering, in the interviews, the alternative toponymy as well, that is, unofficial, vernacular, trying to motivate the interlocutor to seek, in his memory, the identity of such name and its relation to the life of those who live(d) there, whether from the social, political, economic or religious point of view.